Single-crystal positive electrode material, preparation method thereof and secondary battery
Through the method of producing a limited domain molten salt, the molten salt is laid flat on the surface of the precursor material, and the excessive accumulation and spontaneous diffusion of the molten salt are used to form a single crystal positive electrode material, which solves the problem that the materials in the prior art are difficult to sinter into single crystals at a lower temperature, and achieves efficient and low-cost preparation of single crystal positive electrode material.
Patent Information
- Application Number
- CN202411802180.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to sinter a small-particle precursor material into a single-crystal positive electrode material at a lower temperature, and it is difficult for medium- and large-particle precursor materials to form single-crystal particles at conventional sintering temperatures, resulting in increased use of fluxes and excessive molten salts and high production costs.
By laying the molten salt flat on the surface of the precursor material, the domain-limited molten salt is prepared, and the excessive accumulation and spontaneous diffusion of the molten salt is used to promote the mutual melting and growth of primary grains to form a single crystal positive electrode material.
The small-particle size precursor material forms single crystal particles at a lower temperature, so that the medium- and large-particle size precursor material forms single crystal particles at a conventional sintering temperature, reduces the use of flux and excessive molten salt, reduces the production cost, and avoids damage to the crystal structure of the material by high sintering temperature.
Smart Images

Figure CN119612615A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a single crystal positive electrode material and a preparation method thereof and a secondary battery. Background Art
[0002] In recent years, as the new energy industry continues to mature, the use of batteries in energy storage and power fields has continued to rise, and correspondingly, more stringent requirements have been put forward for battery safety and calendar life parameters. As the key core material in the battery, the positive electrode material directly affects the battery life and safety threshold.
[0003] Compared with polycrystalline or quasi-single crystals, single crystal positive electrodes have longer cycle life and excellent safety performance. Large-particle precursors are difficult to grow and disperse into single crystal positive electrodes at high-temperature sintering temperatures; medium-particle precursors often form quasi-single crystals under high-temperature sintering; small-particle precursors are sintered into single crystals at higher temperatures and require additional flux, which increases production costs; although higher temperatures and a large excess of lithium salts can easily sinter medium and large-particle precursors into micron single crystal positive electrode particles, the materials produced have low electrical properties and high costs, making it difficult to meet the needs of battery production.
[0004] In view of this, this invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a method for preparing a single crystal positive electrode material, which can enable a small-particle precursor material to form single crystal particles at a relatively low temperature, and a medium- and large-particle precursor material to form single crystal particles at a conventional sintering temperature, thereby reducing the use of flux and the addition of excess molten salt.
[0006] The second object of the present invention is to provide a single crystal positive electrode material.
[0007] A third object of the present invention is to provide a secondary battery.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a method for preparing a single crystal positive electrode material, comprising the following steps:
[0010] S1, spreading molten salt on the surface of the precursor material to obtain a sintering raw material;
[0011] S2, performing a first sintering and a crushing on the sintering raw material in sequence to obtain a crushed material;
[0012] S3, after mixing the crushed material and the residue remover, performing a second sintering to obtain the single crystal positive electrode material.
[0013] Further, in step S1, the precursor material includes at least one of hydroxide, carbonate, oxide and oxalate;
[0014] And / or, the average particle size of the precursor material is 2 to 18 μm.
[0015] Furthermore, step S1 includes at least one of the following features (1) to (3);
[0016] (1) The molten salt comprises lithium salt and / or sodium salt;
[0017] (2) The lithium salt includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, lithium acetate and lithium oxalate;
[0018] (3) The sodium salt includes at least one of sodium hydroxide, sodium oxide, sodium carbonate, sodium nitrate and sodium oxalate.
[0019] Furthermore, in step S1, the molar ratio of lithium ions and / or sodium ions in the molten salt to the precursor material is (1.01-1.08):1.
[0020] Further, in step S2, the first sintering includes: heating to 400-600° C. and keeping the temperature for 1-5 hours, then heating to 740-1000° C. and keeping the temperature for 8-15 hours;
[0021] And / or, the heating rate of the first sintering is 2-10° C. / min.
[0022] Further, step S3 includes at least one of the following features (1) to (3);
[0023] (1) The residual remover comprises a residual lithium remover and / or a residual sodium remover;
[0024] (2) the residual lithium removal agent comprises at least one of cobalt hydroxide, cobalt oxyhydroxide, niobium pentoxide, ammonium phosphate, titanium dioxide, manganese hydroxide, tungsten trioxide, zirconium dioxide, vanadium pentoxide, boron trioxide, boric acid, ammonium fluoride, silicic acid, aluminum hydroxide, aluminum oxide, tantalum oxide, molybdenum oxide, magnesium oxide and cerium oxide;
[0025] (3) The residual sodium removing agent includes at least one of copper oxide, copper hydroxide, cobalt oxyhydroxide, cobalt hydroxide, cobalt oxide, niobium pentoxide, ammonium phosphate, silicon oxide, titanium dioxide, manganese hydroxide, tungsten trioxide, zirconium dioxide, vanadium pentoxide, boron trioxide, boric acid, ammonium fluoride, aluminum hydroxide, magnesium oxide, aluminum oxide, zinc hydroxide and zinc oxide.
[0026] Furthermore, in step S3, the mass of the residue remover is 0.01% to 0.9% of the mass of the crushed material.
[0027] Furthermore, in step S3, the second sintering includes: heating to 300-950° C. and maintaining the temperature for 1-10 hours.
[0028] In a second aspect, the present invention further provides a single crystal positive electrode material, which is prepared by the method for preparing the single crystal positive electrode material as described above.
[0029] In a third aspect, the present invention further provides a secondary battery comprising the single crystal positive electrode material as described above.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The method for preparing single-crystal positive electrode materials by confined molten salt provided by the present invention utilizes the excessive accumulation of molten salt in a local area and the spontaneous diffusion behavior of the molten salt when it is melted to promote the mutual melting and growth of primary grains, so as to obtain positive electrode materials with micron-sized single-crystal particles; it can enable small-particle precursor materials to form single-crystal particles at a relatively low temperature, and enable medium- and large-particle precursor materials to form single-crystal particles at a conventional sintering temperature, thereby reducing the use of flux and the addition of excess molten salt, and also effectively avoiding the damage to the integrity of the material's crystal structure caused by higher sintering temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is a SEM image of the hydroxide with a particle size D50 of 10 μm in Example 1 of the present invention.
[0034] Figure 2 This is a SEM image of the first sintered material in Example 1 of the present invention.
[0035] Figure 3 This is a SEM image of the hydroxide with a particle size D50 of 4.5 μm in Example 2 of the present invention.
[0036] Figure 4 This is a SEM image of the first sintered material in Example 2 of the present invention.
[0037] Figure 5 This is a SEM image of the first sintered material in Comparative Example 1 of the present invention.
[0038] Figure 6 This is a SEM image of the first sintered material in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0039] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0040] The following is a detailed description of a single crystal positive electrode material, a preparation method thereof, and a secondary battery of the present invention.
[0041] In some embodiments of the present invention, a method for preparing a single crystal positive electrode material is provided, comprising the following steps:
[0042] S1, spreading molten salt on the surface of the precursor material to obtain a sintering raw material;
[0043] S2, performing a first sintering and a crushing on the sintering raw material in sequence to obtain a crushed material;
[0044] S3, after mixing the crushed material and the residue remover, perform a second sintering to obtain a single crystal positive electrode material.
[0045] The method for preparing the single crystal positive electrode material of the present invention is to spread the precursor material underneath during sintering of the single crystal, and then spread the molten salt on the surface of the precursor material, so that the molten salt completely covers the surface of the precursor material. There is no need for the mixing step during conventional sintering, which effectively shortens the synthesis process. In addition, there is no need to add additional flux for auxiliary sintering or excess molten salt, thereby reducing the cost of production auxiliary materials.
[0046] The present invention utilizes the excessive accumulation of molten salt in a local area and the spontaneous diffusion behavior of the molten salt when it is melted, such as the spontaneous diffusion behavior from lithium-rich / sodium-rich positions to lithium-deficient / sodium-deficient positions when lithium salt / sodium salt is melted, to promote the mutual melting and growth of primary grains, so that small-particle precursor materials can form single crystal particles at a relatively low temperature, and medium- and large-particle precursor materials can form single crystal particles at a conventional single crystal sintering temperature, thereby achieving the effect of lowering the sintering temperature and enhancing the sintering effect, and effectively avoiding the damage to the integrity of the material's crystal structure caused by high sintering temperature.
[0047] The present invention mixes the crushed material and the residue remover and then performs a second sintering, which can repair the structure and remove residual metals on the surface, such as residual lithium or residual sodium. The second sintering effectively reduces the negative impact of residual lithium or residual sodium impurities that have not completely entered the crystal structure on the crystal structure and electrical properties.
[0048] The method for preparing single crystal positive electrode materials of the present invention is a method for preparing single crystal positive electrode materials by confined molten salt, which can effectively solve the technical problems that medium and large particle size precursor materials are difficult to sinter into single crystal positive electrode materials and the high temperature required for sintering small particle size precursor materials into single crystal positive electrode materials.
[0049] In some embodiments of the present invention, in step S1, the molten salt and the precursor material are alternately laid; a layer of molten salt and a layer of precursor material laid alternately are an alternating unit, and the number of alternating units is greater than or equal to 1, for example, it can be 1, 2, 3, 4, etc.
[0050] In some embodiments of the present invention, in step S1, the precursor material includes at least one of hydroxide, carbonate, oxide and oxalate; preferably, the precursor material includes Ni x Co y Mn 1-x-y (OH)2、Ni x Fe y Mn 1-x-y (OH)2、Ni x Co y Mn 1-x-y CO3、Ni x Fe y Mn 1-x-y CO3、Ni x Co y Mn 1-x-y C2O4、Ni x Fe y Mn 1-x-y C2O4、Ni x Co y Mn 1-x-y O2 and Ni x Fe y Mn 1-x-y At least one of O2; wherein, x>0, y>0, 0<1-xy<1.
[0051] In some embodiments of the present invention, in step S1, the average particle size D50 of the precursor material is 2 to 18 μm; typically but not limitatively, for example, the average particle size D50 of the precursor material can be 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or a range of any two thereof.
[0052] In some embodiments of the present invention, in step S1, the molten salt includes lithium salt and / or sodium salt.
[0053] In some embodiments of the present invention, in step S1, the lithium salt includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, lithium acetate and lithium oxalate.
[0054] In some embodiments of the present invention, in step S1, the sodium salt includes at least one of sodium hydroxide, sodium oxide, sodium carbonate, sodium nitrate and sodium oxalate.
[0055] In some embodiments of the present invention, in step S1, the molar ratio of lithium ions and / or sodium ions in the molten salt to the precursor material is (1.01-1.08):1; typically but not limitatively, for example, the molar ratio of lithium ions and / or sodium ions in the molten salt to the precursor material can be 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1 or a range of any two thereof.
[0056] In some embodiments of the present invention, in step S2, the first sintering includes: heating to 400-600°C (for example, 400°C, 450°C, 500°C, 550°C, 600°C or a range of any two thereof) and heat preservation for 1-5h (for example, 1h, 2h, 3h, 4h, 5h or a range of any two thereof), and then heating to 740-1000°C (for example, 740°C, 800°C, 900°C, 1000°C or a range of any two thereof) and heat preservation for 8-15h (for example, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or a range of any two thereof).
[0057] In some embodiments of the present invention, in step S2, the heating rate of the first sintering is 2 to 10°C / min; typically but not limitatively, for example, the heating rate of the first sintering can be 2°C / min, 5°C / min, 7°C / min, 10°C / min or a range of any two thereof.
[0058] In some embodiments of the present invention, in step S2, the first sintering is performed in air or oxygen atmosphere.
[0059] In some embodiments of the present invention, in step S3, the residual removing agent includes a residual lithium removing agent and / or a residual sodium removing agent.
[0060] In some embodiments of the present invention, in step S3, the residual lithium removing agent includes at least one of cobalt hydroxide, cobalt oxyhydroxide, niobium pentoxide, ammonium phosphate, titanium dioxide, manganese hydroxide, tungsten trioxide, zirconium dioxide, vanadium pentoxide, boron trioxide, boric acid, ammonium fluoride, silicic acid, aluminum hydroxide, aluminum oxide, tantalum oxide, molybdenum oxide, magnesium oxide and cerium oxide.
[0061] In some embodiments of the present invention, in step S3, the residual sodium removing agent includes at least one of copper oxide, copper hydroxide, cobalt oxyhydroxide, cobalt hydroxide, cobalt oxide, niobium pentoxide, ammonium phosphate, silicon oxide, titanium dioxide, manganese hydroxide, tungsten trioxide, zirconium dioxide, vanadium pentoxide, boron trioxide, boric acid, ammonium fluoride, aluminum hydroxide, magnesium oxide, aluminum oxide, zinc hydroxide and zinc oxide.
[0062] In some embodiments of the present invention, in step S3, the mass of the residue remover is 0.01% to 0.9% of the mass of the crushed material; typically but not limiting, for example, the mass of the residue remover is 0.01%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 0.9% of the mass of the crushed material or a range consisting of any two of them.
[0063] In some embodiments of the present invention, in step S3, the second sintering includes: heating to 300-950°C and keeping warm for 1-10 hours; typically but not limitatively, for example, the temperature of the second sintering can be 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or a range of any two thereof; the time of the second sintering can be 1h, 2h, 4h, 6h, 8h, 10h or a range of any two thereof.
[0064] In some embodiments of the present invention, in step S3, the heating rate of the second sintering is 1-5°C / min.
[0065] In some embodiments of the present invention, in step S3, the second sintering is performed in air or oxygen atmosphere.
[0066] In some embodiments of the present invention, when the molten salt is a lithium salt, the residue remover is a lithium residue remover, and the single crystal positive electrode material obtained is a lithium battery positive electrode material; when the molten salt is a sodium salt, the residue remover is a sodium residue remover, and the single crystal positive electrode material obtained is a sodium battery positive electrode material.
[0067] The precursor material is Ni 0.6 Co 0.1 Mn 0.3 (OH)2 as an example, when Ni 0.6 Co 0.1 Mn 0.3The average particle size of (OH)2 is 2-5 μm. The first sintering includes: heating to 400-600℃ and keeping heat for 1-5 hours, then heating to 820-870℃ and keeping heat for 8-15 hours. The second sintering includes: heating to 300-950℃ and keeping heat for 1-10 hours. When Ni x Co y Mn 1-x-y The average particle size of (OH)2 is 5.1-18 μm. The first sintering includes: heating to 400-600°C and keeping heat for 1-5 hours, then heating to 871-920°C and keeping heat for 8-15 hours. The second sintering includes: heating to 300-950°C and keeping heat for 1-10 hours.
[0068] In some embodiments of the present invention, a single crystal positive electrode material is also provided, which is prepared by the above-mentioned method for preparing the single crystal positive electrode material.
[0069] The single crystal positive electrode material prepared by the method for preparing the single crystal positive electrode material of the present invention has excellent electrochemical performance.
[0070] In some embodiments of the present invention, the single crystal positive electrode material is a single crystal particle with a particle size D50 of 2 to 5 μm and a tap density of 1.4 to 2.3 g / cm 3 .
[0071] In some embodiments of the present invention, a secondary battery is provided, comprising the above-mentioned single crystal positive electrode material.
[0072] In some embodiments of the present invention, the secondary battery comprises a sodium ion battery or a lithium ion battery.
[0073] Example 1
[0074] The method for preparing the single crystal positive electrode material provided in this embodiment comprises the following steps:
[0075] S1, weigh 1 mol of hydroxide (chemical formula is Ni 0.6 Co 0.1 Mn 0.3 (OH)2, particle size D50 is 10 μm) and 1.07 mol lithium hydroxide, first spread the hydroxide, and then spread the lithium hydroxide on the surface of the hydroxide to obtain a sintering raw material;
[0076] S2. In an air atmosphere, the sintering raw material is heated from room temperature to 400° C. and kept for 3 hours, and then heated to 900° C. and kept for 11 hours, with a heating rate of 7° C. / min, to obtain a first sintering material; the first sintering material is subjected to air flow pulverization to obtain a pulverized material;
[0077] S3. Mix the crushed material with cobalt hydroxide in a high-speed mixer, with the mass of cobalt hydroxide being 0.5% of the mass of the crushed material. Then, heat the mixture to 750°C in an air atmosphere and keep the mixture for 8 hours at a heating rate of 2°C / min. Then, cool the mixture to room temperature to obtain a single crystal positive electrode material (lithium battery positive electrode material).
[0078] Example 2
[0079] The method for preparing the single crystal positive electrode material provided in this embodiment comprises the following steps:
[0080] S1, weigh 1 mol of hydroxide (chemical formula is Ni 0.334 Fe 0.333 Mn 0.333 (OH)2, particle size D50 is 4.5 μm) and 1.05 mol sodium hydroxide, first spread the hydroxide, and then spread the sodium hydroxide on the surface of the hydroxide to obtain a sintering raw material;
[0081] S2. In an air atmosphere, the sintering raw material is heated from room temperature to 400° C. and kept for 3 hours, and then heated to 900° C. and kept for 13 hours, with a heating rate of 5° C. / min, to obtain a first sintering material; the first sintering material is subjected to air flow pulverization to obtain a pulverized material;
[0082] S3. Under air atmosphere, the crushed material and copper oxide are mixed in a high-speed mixer, the mass of copper oxide is 0.8% of the mass of the crushed material, and then the temperature is raised to 900°C for heat treatment for 5 hours at a heating rate of 3°C / min, and cooled to room temperature to obtain a single crystal positive electrode material (sodium positive electrode material).
[0083] Example 3
[0084] The preparation method of the single crystal positive electrode material provided in this embodiment refers to Example 1, with the only difference being that in step S1, the particle size D50 of the hydroxide is 3.5 μm; in step S2, the sintering raw material is heated from room temperature to 400°C and kept for 3 hours, and then heated to 870°C and kept for 11 hours.
[0085] Example 4
[0086] The preparation method of the single crystal positive electrode material provided in this embodiment refers to Example 2, with the only difference being that in step S1, the particle size D50 of the hydroxide is 8 μm; in step S2, the sintering raw material is heated from room temperature to 400°C for 3 hours, and then heated to 950°C for 9 hours.
[0087] Example 5
[0088] The preparation method of the single crystal positive electrode material provided in this embodiment refers to that in embodiment 1, the only difference is that in step S1, the particle size D50 of the hydroxide is 2 μm; in step S2, the sintering raw material is heated from room temperature to 400°C and kept for 3 hours, and then heated to 850°C and kept for 11 hours.
[0089] Example 6
[0090] The preparation method of the single crystal positive electrode material provided in this embodiment refers to that in Embodiment 1, the only difference is that in step S1, the particle size D50 of the hydroxide is 18 μm; in step S2, the sintering raw material is heated from room temperature to 400°C and kept for 3 hours, and then heated to 900°C and kept for 14 hours.
[0091] Example 7
[0092] The preparation method of the single crystal positive electrode material provided in this embodiment refers to Example 1, with the only difference being that in step S3, the crushed material and boron trioxide are mixed in a high-speed mixer, the mass of boron trioxide being 0.25% of the mass of the crushed material, and then the temperature is raised to 300° C. and kept for 5 hours in an air atmosphere.
[0093] Example 8
[0094] The preparation method of the single crystal positive electrode material provided in this embodiment refers to that in embodiment 1, the only difference is that in step S1, 1 mol of hydroxide (chemical formula is Ni 0.6 Co 0.1 Mn 0.3 (OH)2, particle size D50 is 10μm) and 1.07mol lithium hydroxide. First, spread the hydroxide, then spread the lithium hydroxide on the surface of the hydroxide, and then repeat the alternating spreading of hydroxide and lithium hydroxide on the surface, repeat twice to obtain the sintering raw material.
[0095] Comparative Example 1
[0096] The preparation method of the positive electrode material provided in this comparative example refers to Example 1, and the only difference is that in step S1, the hydroxide and lithium hydroxide are mixed in a high-speed mixer to obtain a sintering raw material.
[0097] Comparative Example 2
[0098] The preparation method of the positive electrode material provided in this comparative example refers to comparative example 1, with the only difference being that in step S2, the sintering raw material is heated from room temperature to 400°C for 3 hours, and then heated to 950°C for 11 hours, with a heating rate of 7°C / min.
[0099] Comparative Example 3
[0100] The preparation method of the positive electrode material provided in this comparative example refers to Example 2, the only difference being that in step S1, the hydroxide and sodium hydroxide are mixed in a high-speed mixer to obtain a sintering raw material.
[0101] Comparative Example 4
[0102] The preparation method of the positive electrode material provided in this comparative example refers to comparative example 3, with the only difference being that in step S2, the sintering raw material is heated from room temperature to 400°C for 3 hours, and then heated to 980°C for 13 hours, with a heating rate of 5°C / min.
[0103] Test example
[0104] SEM tests were performed on the hydroxide and the first sintered material with a particle size D50 of 10 μm in Example 1, the hydroxide and the first sintered material with a particle size D50 of 4.5 μm in Example 2, the first sintered material in Comparative Example 1, and the first sintered material in Comparative Example 3. The results are as follows: Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 shown.
[0105] from Figure 1 to Figure 6 It can be seen that after the large-particle hydroxide precursor material of Example 1 and the lithium salt are first sintered, and after the medium-particle hydroxide precursor material of Example 2 and the sodium salt are first sintered, single-crystal positive electrode material particles with good dispersion are obtained. However, in Comparative Examples 1 and 3, the positive electrode material particles obtained by sintering after the precursor material and the lithium salt / sodium salt are evenly mixed still appear as polycrystalline particles, which are difficult to crack into single crystal particles. Therefore, the method of confined molten salt sintering of the present invention can effectively reduce the sintering temperature and obtain single-crystal positive electrode material particles.
[0106] The electrochemical properties of the single crystal positive electrode materials of Examples 1 to 8 and the positive electrode materials prepared in Comparative Examples 1 to 4 were tested, and the results are shown in Table 1. The materials prepared in Example 1, Example 3, and Comparative Examples 1 to 2 are lithium positive electrode materials; the materials prepared in Example 2, Example 4, and Comparative Examples 3 to 4 are sodium positive electrode materials.
[0107] Lithium battery positive electrode material: After dispersing lithium battery positive electrode material, carbon tube conductive agent and binder in NMP solvent at a mass ratio of 96:2:2, it is coated on aluminum sheet and cut into circular positive electrode sheet for use. In the glove box, the positive electrode sheet is combined with lithium sheet, diaphragm and electrolyte to form a soft pack battery; then the battery performance is tested in the voltage range of 2.8 to 4.3V.
[0108] Sodium positive electrode material: Sodium positive electrode material, carbon tube conductive agent, and binder are dispersed in NMP solvent at a mass ratio of 96:2:2, and then coated on aluminum sheets, which are cut into circular positive electrode sheets for use. In a glove box, the positive electrode sheets are combined with sodium sheets, diaphragms, and electrolytes to form soft-pack batteries; then the battery performance is tested in the voltage range of 2.0 to 4.0 V.
[0109] Table 1
[0110]
[0111]
[0112] As can be seen from Table 1, the single crystal positive electrode material particles prepared by the present invention have higher capacity and cycle stability, which are better than the positive electrode material cycle stability and capacity obtained in the comparative example. Therefore, the preparation method of the single crystal positive electrode material of the present invention can effectively solve the technical problems that medium and large particle size precursor materials are difficult to sinter into single crystal positive electrode materials and small particle size precursor materials require high temperatures to sinter into single crystal positive electrode materials.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a single crystal positive electrode material, characterized in that: The steps include: S1, spreading molten salt on the surface of the precursor material to obtain a sintering raw material; S2, performing a first sintering and a crushing on the sintering raw material in sequence to obtain a crushed material; S3, after mixing the crushed material and the residue remover, performing a second sintering to obtain the single crystal positive electrode material.
2. The method for preparing a single crystal positive electrode material according to claim 1, characterized in that: In step S1, the precursor material includes at least one of hydroxide, carbonate, oxide and oxalate; And / or, the average particle size of the precursor material is 2 to 18 μm.
3. The method for preparing a single crystal positive electrode material according to claim 1, characterized in that: In step S1, at least one of the following features (1) to (3) is included; (1) The molten salt comprises lithium salt and / or sodium salt; (2) The lithium salt includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, lithium acetate and lithium oxalate; (3) The sodium salt includes at least one of sodium hydroxide, sodium oxide, sodium carbonate, sodium nitrate and sodium oxalate.
4. The method for preparing a single crystal positive electrode material according to claim 1, characterized in that: In step S1, the molar ratio of lithium ions and / or sodium ions in the molten salt to the precursor material is (1.01-1.08):
1.
5. The method for preparing a single crystal positive electrode material according to claim 4, characterized in that: In step S2, the first sintering includes: heating to 400-600°C and keeping the temperature for 1-5 hours, then heating to 740-1000°C and keeping the temperature for 8-15 hours; And / or, the heating rate of the first sintering is 2-10° C. / min.
6. The method for preparing a single crystal positive electrode material according to claim 5, characterized in that: In step S3, at least one of the following features (1) to (3) is included; (1) The residual remover comprises a residual lithium remover and / or a residual sodium remover; (2) the residual lithium removal agent comprises at least one of cobalt hydroxide, cobalt oxyhydroxide, niobium pentoxide, ammonium phosphate, titanium dioxide, manganese hydroxide, tungsten trioxide, zirconium dioxide, vanadium pentoxide, boron trioxide, boric acid, ammonium fluoride, silicic acid, aluminum hydroxide, aluminum oxide, tantalum oxide, molybdenum oxide, magnesium oxide and cerium oxide; (3) The residual sodium removing agent includes at least one of copper oxide, copper hydroxide, cobalt oxyhydroxide, cobalt hydroxide, cobalt oxide, niobium pentoxide, ammonium phosphate, silicon oxide, titanium dioxide, manganese hydroxide, tungsten trioxide, zirconium dioxide, vanadium pentoxide, boron trioxide, boric acid, ammonium fluoride, aluminum hydroxide, magnesium oxide, aluminum oxide, zinc hydroxide and zinc oxide.
7. The method for preparing a single crystal positive electrode material according to claim 5, characterized in that: In step S3, the mass of the residue remover is 0.01% to 0.9% of the mass of the crushed material.
8. The method for preparing a single crystal positive electrode material according to claim 5, characterized in that: In step S3, the second sintering includes: heating to 300-950°C and maintaining the temperature for 1-10 hours.
9. A single crystal positive electrode material, characterized in that: The single crystal positive electrode material is prepared by the method for preparing the single crystal positive electrode material according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: Comprising the single crystal positive electrode material as described in claim 9.